Association of Polymorphisms in Toll-Like Receptors 4 and 9 with Autoimmune Thyroid Disease in Korean Pediatric Patients - Won Kyoung Cho; Jung-Pil Jang; Eun-Jeong Choi; Moonbae Ahn; Shin Hee Kim; Kyoung Soon Cho; So Hyun Park; In Cheol Baek; Min Ho Jung; Tai-Gyu Kim; Byung-Kyu Suh (International Journal of Endocrinology)
Background. Toll-like receptors (TLRs) have been suggested to be associated with the development of AITD. Methods. Fifteen single-nucleotide polymorphisms in 7 TLR genes were analyzed in 104 Korean children (girls = 86, boys = 18) with AITD (Hashimoto disease (HD) = 44, Graves’ disease (GD) = 60, thyroid-associated ophthalmopathy (TAO) = 29, and non-TAO = 31) with 183 controls. Results. GD showed higher frequencies of the TLR4 rs1927911 C allele than control. TAO showed a lower frequency of the TLR4 rs1927911 CT genotype and non-TAO showed a higher frequency of the TLR4 rs1927911 CC genotype than control. The frequency of the TLR9 rs187084 CC genotype in TAO was higher than that in non-TAO. GD females showed a higher frequency of the TLR4 rs10759932 T allele, rs1927911 CC genotype, and the rs1927911 C allele than controls. GD males showed a higher frequency of the TLR4 rs10759932 CC genotype and rs1927911 TT genotype and lower frequency of the rs1927911 CT genotype than control. The frequency of the TLR4 rs10759932 CC genotype, C allele and rs1927911 TT genotype, and T allele in a GD female were lower than in a GD male. Conclusions. Our results suggest that TLR4 and 9 polymorphisms might contribute to the pathogenesis of GD and TAO.